The role of over-indebtedness stress and trait resilience on work withdrawal in the workplace - Atienza, Ringgold P. (Animo Repository, 2025)
Stress from massive personal financial obligations has become an increasing concern globally and locally. The literature showed strong evidence of the grave consequences of indebtedness that result in an individual’s decreased overall wellness. This study explores how indebtedness stress affects the work behavior of employees. This study utilized the experience sampling methodology (ESM), which identifies the behavior patterns within an individual over time. The 35 employees who experienced over-indebtedness were subjected to this record of their daily personal indebtedness stress, threat appraisal on stress, self-regulation depletion, and work withdrawal. The study revealed the positive indirect effect of indebtedness stress on self-regulation depletion through threat appraisal and the positive indirect effect of financial stress on work withdrawal through threat appraisal and self-regulation depletion. The result means that indebtedness stress can persist when employees lack social support. Moreover, resilience was also shown to have a significant role in the effect of indebtedness stress on workplace withdrawal. This study provides revelatory insights into indebtedness research, considering the dearth of literature on indebtedness stress in the organizational setting. The results of this study can provide insights to help managers understand and deal with employees experiencing work-life interference problems; specifically employees having debt problems.